14 Incidental detection of thyroid abnormalities on low-dose computed tomography in the national lung screening trial. (20th August 2018) - Loomans, Holli; Pinsky, Paul; Dunn, Barbara; Kramer, Barnett
Abstract : Objectives: Overdiagnosis, diagnosis of a cancer that would not ultimately cause symptoms or death, has become relatively common in a variety of cancers, including thyroid cancer (ThCa). The trend of ThCa incidence, which has increased substantially without a corresponding change in mortality, typifies overdiagnosis. An analysis of Surveillance, Epidemiology, and End Results (SEER) program data has suggested that overdiagnosis may be responsible for up to 60% of diagnosed papillary ThCa cases, the most common histotype of ThCa. Our main objective is to assess whether thyroid abnormalities discovered incidentally on imaging studies carried out in the National Lung Screening Trial (NLST) are associated with overdiagnosis. Method: The National Lung Screening Trial (NLST), a randomized trial of almost 54 000 current and former smokers that compared low-dose computed tomography (LDCT) to chest radiography (CXR) for the early detection of lung cancer, is a resource to investigate the potential impact of incidental overdiagnosis of ThCa even when screening for an unrelated cancer in anatomic proximity to the thyroid gland. Previously, Pinsky and colleagues used NLST data to examine renal-related abnormalities outside the intended lung field and found that renal tumors could be incidentally detected by LDCT. A similar phenomenon can be investigated in ThCa, examining the upper portion of the LDCT field. Results: Preliminary analyses show more diagnosed thyroid cancers in the LDCT as compared to CXR arm during the screening phase (first 3 years) of the trial (23 versus 11) and overall (35 versus 25). We will examine the relationship of reported thyroid abnormalities on LDCT and subsequent diagnoses of thyroid cancer. Specifically, we will assess the proportion of thyroid cancers diagnosed within one year of an LDCT screen that had a reported thyroid abnormality, as well as the overall rate of thyroid abnormalities seen on LDCT screens. We will also examine survival of thyroid cancers by trial arm and mode of diagnosis (observed on LDCT scan or not). Conclusions: Preliminary data suggest that more thyroid cancers were diagnosed in the LDCT than in the CXR arm. This suggests a possible association of overdiagnosis of ThCa with the more sensitive screening technology (LDCT).